Biointerfaces: Porous Silicon Nanoneedles Modulate Endocytosis to Deliver Biological Payloads (Adv. Mater. 12/2019). Issue 12 (19th March 2019) - Gopal, Sahana; Chiappini, Ciro; Penders, Jelle; Leonardo, Vincent; Seong, Hyejeong; Rothery, Stephen; Korchev, Yuri; Shevchuk, Andrew; Stevens, Molly M.
Abstract : In article number 1806788, Ciro Chiappini, Andrew Shevchuk, Molly M. Stevens, and co‐workers show that porous silicon nanoneedles stimulate endocytic activity in mesenchymal stem cells. Endocytic pits localize around the nanoneedles leading to increased uptake of pathway‐specific payloads and their endolysosomal trafficking, yet nucleic acids delivered from nanoneedles retain their biological activity, suggesting the overlap of concurrent delivery mechanisms. These findings significantly advance the current understanding of the mechanisms of intracellular delivery by nanoinjection.